Green Open Space Needs Analysis of Carbon Dioxide (Co2) Gas Emissions Absorbtion in Serang City - Masyruroh, Anis; M Hartono, Djoko; Haeruman, Herman; Hadisuganda, Emir (International Journal of Engineering and Technology, 2018)
An increasing number of population in Serang has resulted in the diversion of vegetated land function to be built area, thus reducing total area of green open space (RTH) of the city. Impact of the land conversion increase will occur on the increasing area of land cover. Land cover thus reduced the vegetation ability to absorb CO2, so that the CO2 generated from activities in the city, such as from energy consumption, livestock and landfill waste cannot be absorbed optimally. The purpose of this study were: 1) to analyze the amount of CO2 emissions from energy use, livestock and garbage activities in 2016-2026; 2) to analyze the CO2 absorption by green space area; 3) to analyze RTH Needs of 2016-2026 to absorb CO2. gas emission. This study was conducted in May 2016 to September 2016. The method used in this research was IPCC calculation for the calculation of emissions from garbage, livestock, and electrical energy. Based on the results of the study showed that in 2016 the Serang city need of green space area was 9844.79 hectares to absorb CO2 gas emissions by 511,051.61 and in 2026Â green space area needs of Serang city to absorb CO2 emissions by 18.168 tons was a total area of 1,058,468.16, 76 hectares.Â Â